KNOWLEDGE SHARING LINTAS KEILMUAN MELALUI WEB-BASED SEMINAR DI MASA WORK FROM HOME - Zaenal Abidin Eko Putro; Ida Nurhayati; Iis Maria; Anis Rosyidah; Iwan Susanto; Novi Purnama Sari (Politeknik Negeri Sriwijaya, 2020)
Implementing protocols in responding pandemic covid19, that are distance learning and work from home, causes an unexpected thing toward academic atmosphere in higher education. Learning process that previously done by face to face interaction is suddenly replaced by online learning. Some difficulties are not merely affected campus’ academia, but also public intellectuals who gather in an association including Indonesia’ Centre of Asian Studies (CENAS). Aside of learning, face to face discussion among lecturers as well as public intellectuals to share some new information about research result could not also be hled. In this sense, there has been a concerned issue about decreasing the spirit of knowledge and information sharing among intellectuals. To respond the anxiety, UP2M as a research centre of the Politeknik Negeri Jakarta in collaboration with its partner, Indonesia’ Centre of Asian Studies (CENAS), hosts an online seminar or widely known as web-based seminar (webinar). All the distinguish speakers are from the Politeknik Negeri Jakarta who have been known for their eagerness in doing research. As a result, arranging this webinar has meant that readiness of all civitas academia to suit themselves with the situation of online learning that is unavoidable during the current pandemic covid-19.